The Determinants of New Product Performance in Malaysian Industry - Fok-Yew, Oon (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2014)
The literature on new product development is growing but Malaysia manufacturing industry often lacks these discussions. Therefore, this paper focuses on linking the determinants of an effective product development process and new product performance within manufacturing companies across industries in Malaysia that have certain level of new product development activities taking in their organization. Further, the paper organises the burgeoning new product development literature into four main determinants: customer orientation, cross-functional team, new product development team proficiency and management support. The selection of determinants to the theoretical framework is adjusting for manufacturing industry origins in previous written research material. The literature review focuses on the product development process and builds the framework of conceptual model detailing the initialization and implementation stage in the product development process. Two theoretical perspectives have guided the conceptual framework which is the resource-based view and organizational theories. The proposal is to give an increased understanding of the changed new product process in Malaysian industry and its implication on activities concerning organisation and management of the new product development process. This framework reflects a growing interest in extending new product development paradigms to emerging in ASEAN countries, thus contributing to a wider body of knowledge.